Molecular and functional studies of retinal degeneration as a clinical presentation of SACS-related disorder. (July 2015) - Blumkin, Lubov; Bradshaw, Teisha; Michelson, Marina; Kopler, Tal; Dahari, Dvir; Lerman-Sagie, Tally; Lev, Dorit; Chapple, J. Paul; Leshinsky-Silver, Esther
Abstract Background ARSACS (autosomal–recessive spastic ataxia of Charlevoix-Saguenay) is a neurodegenerative disorder caused by SACS gene mutations and characterized by a triad of symptoms: early-onset cerebellar ataxia, spasticity and peripheral neuropathy. A characteristic retinal nerve fiber hypertrophy has been reported in several individuals with ARSACS. Methods We describe a patient with a unique clinical presentation of ataxia, nystagmus, dysarthria, hearing impairment, and retinal degeneration. Whole-exome-sequencing was performed as well as morphological studies in the patient's fibroblasts. Results A compound heterozygosity for a novel D3269N and N2380K mutations in the SACS gene was found. The parents are carriers. Morphological studies revealed a dramatic decrease in the number of cell mitochondria as well as a difference in mitochondrial network morphology. Conclusions Retinal degeneration has never been reported in ARSACS. Since sacsin is involved in the mitochondrial fusion-fission process, we speculate that defected fission process may be responsible for an impaired mitochondrial function and retinal degeneration. Our patient has a unique clinical presentation of SACS mutations inconsistent with the classic ARSACS triad but also different from the "atypical" presentations described in the literature. Further studies are necessary to clarify the factors that modify the SACS related phenotype.